Profil Aktivitas Antioksidan Ekstrak Polar dan Non-Polar Umbi Porang (Amorphophallus muelleri Blume) Menggunakan Uji DPPH - Nova Ria Ovelti Sihotang; Roy Indrianto Bangar; Hariyadi Dharmawan Syahputra (Herbal Medicine Journal, 2026)
Porang tuber (Amorphophallus muelleri Blume) is an Indonesian native commodity rich in glucomannan polysaccharides and potentially serves as a natural antioxidant source to counteract free radicals that trigger degenerative diseases. Objective of the researchv to map the antioxidant activity profile of non-polar, semi-polar, and polar extract s of porang tuber and determine the IC50 value using the DPPH method. Porang tuber powder was extracted through multilevel maceration using n-hexane, chloroform, ethyl acetate, and ethanol solvents. Antioxidant activity was tested using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method with UV-Vis Spectrophotometry at 517 nm, utilizing Vitamin C and Quercetin as positive controls. Result: The results showed that all extract possessed extremely strong antioxidant activity. The lowest IC50 value was obtained from the ethyl acetate extract at 3.44 ppm, followed by the ethanol extract at 3.61 ppm and the n-hexane extract at 3.81 ppm. The activity of the ethyl acetate extract was stronger than the positive controls, Vitamin C (3.75 ppm) and Quercetin (4.52 ppm). Multilevel extraction is effective in separating the active compounds of porang tuber, with the semi-polar extract (ethyl acetate) exhibiting the most optimal and extremely strong antioxidant potential.